PERAN DAN KONTRIBUSI ULAMA DALAM SISTEM PEMBELAJARAN PESANTREN MODERN AL-HASYIMIYAH CILEGON BANTEN: (Studi Kualitatif Deskriptif Analitis di Pesantren Modern Al-Hasyimiyah Cilegon Banten) - syarifudin syarif (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2021)
ABSTRACT The role and contribution of ulama are really needed in the learning system activities in the Modern Islamic Boarding School because in the modern Islamic boarding schools the executors in teaching and learning activities are not only pesantren leaders or ulama / kiyai as in traditional pesantren or salafi which make the central teaching staff, but also the system has been implemented in modern Islamic Boarding School. so in the learning system that is the role and contribution ulama needed so that students are educated and became graduates according to what is expected by the founders of the pesantren. Based on the background of the problem, the author can formulate the problem as follows: how is the role and contribution ulama? how is the role and contribution of ulama? how is the learning system in al-hasyimiyah modern pesantren? And this study aims to determine: the role and contribution of ulama in the modern pesantren Al-hasyimiyah, the learning system in the modern pesantren Al-Hasyimiyah Cilegon Banten. This research uses the method of Qualitative Field Research in the form of analytical descriptive using data collection techniques and facts through interviews, observation, and documentation. From the results of literature studies and research in the field, it is known that the importance of the role and contribution of ulama in the learning system in modern pesantren Al-Hasyimiyah Cilegon Banten, because of the important role of ulama in modern pesantren Al-Hasyimiyah must be able to implement its role in the learning system in Pesantren. Leaders, ulama, as educators must be able to instill moral values ​​in students to form good morals in students. The thought contribution of this research is in the form of text analysis on the role and contribution in the learning process as input to all stakeholders in the world of pesantren, especially modern pesantren Al-Hasyimiyah Cilegon Banten, so that modern pesantren has superior works in the fields of Arabic and English, religious knowledge, general science and understand all aspects in a scientific manner. Keywords: Ulama, Learning System, Modern Islamic Boarding School.